PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI SAHAM PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN PERIODE 2017 - 2019 - Rizal Indra Tjahya Tjahya; Desiyana Herlin Kusumawati (BALANCING: Accountancy Journal, 2022)
This study aims to see how much influence profitability and liquidity have on the value of food and beverage sub-sector companies for the 2017-2019 period. The determination of the sample used purposive sampling so that the sample obtained was as many as 10 companies. The data analysis techniques used are classical assumption tests, as well as multiple linear regression analysis with the help of SPSS 24. From the results of data processing, it is known that profitability (ROE) has a positive and significant effect on the value of the company (PBV). And the liquidity variable (CR) has a significant effect on the value of the company (PBV).